Dietary behaviours and related lifestyles according to the presence or absence of skipping breakfast in Japanese adults: the JPHC-NEXT study - Chika Okada; Hiroyasu Iso; Kazumasa Yamagishi; Ai Ikeda; Mitsumasa Umesawa; Isao Muraki; Nobufumi Yasuda; Tadahiro Kato; Isao Saito; Kazuhiko Arima; Takayuki Nishimura; Kozo Tanno; et al. (Cambridge University Press, 2023)
Abstract Objective: To assess dietary behaviours and related lifestyles according to the presence or absence of skipping breakfast. Design: We analysed the cross-sectional data from a baseline survey of a large-scale population-based cohort study in Japan conducted in 2011-2016. Participants provided information on dietary behaviours and lifestyles through a self-administered questionnaire. Skipping breakfast was defined as not eating breakfast at least once a week and was classified according to the frequency of skipping breakfast as 1-2, 3-4 or ≥5 times/week. Setting: Sixteen municipalities in seven prefectural areas across Japan under the Japan Public Health Centre-based prospective study for the Next Generation. Participants: 112 785 residents (51 952 males and 60 833 females) aged 40-74 years. Results: After adjustment for age, socio-demographic status, drinking status and smoking status, individuals who skipped breakfast at least once a week, compared with those who ate breakfast every day, were more likely to have adverse dietary behaviours such as frequent eating out (multivariable OR = 2·08, 95 % CI (1·96, 2·21) in males and 2·15, 95 % CI (1·99, 2·33) in females), frequent eating instant foods (1·89, 95 % CI (1·77, 2·01) in males and 1·72, 95 % CI (1·56, 1·89) in females). They had late bedtime (1·85, 95 % CI (1·75, 1·95) in males and 1·98, 95 % CI (1·86, 2·11) in females) and living alone (2·37, 95 % CI (2·17, 2·58) in males and 2·02, 95 % CI (1·83, 2·21) in females), using the logistic regression model. Conclusions: Both adult males and females who skipped breakfast were likely to eat out, to have a dietary habit of eating instant foods and have lifestyles such as late bedtime and living alone than those who ate breakfast.